Endocannabinoids regulate cocaine-associated memory through brain AEA-CB1R signalling activation - Hongchun Li; Rong Chen; Yuanyi Zhou; Haichuan Wang; Luqiang Sun; Zhen Yang; Lin Bai; Jie Zhang (Elsevier, 2022)
Objective: Contextual drug-associated memory precipitates craving and relapse in substance users, and the risk of relapse is a major challenge in the treatment of substance use disorders. Thus, understanding the neurobiological underpinnings of how this association memory is formed and maintained will inform future advances in the treatment of drug addiction. Brain endocannabinoids (eCBs) signalling has been associated with drug-induced neuroadaptations, but the role of lipases that mediate small lipid ligand biosynthesis and metabolism in regulating drug-associated memory has not been examined. Here, we explored how manipulation of the lipase fatty acid amide hydrolase (FAAH), which is involved in mediating the level of the lipid ligand anandamide (AEA), affects cocaine-associated memory formation. Methods: We applied behavioural, pharmacological and biochemical methods to detect cocaine-associated memory formation, eCBs in the dorsal dentate gyrus (dDG), and the activity of related enzymes. We further examined the roles of abnormal FAAH activity and AEA-CB1R signalling in the regulation of cocaine-associated memory formation and granule neuron dendritic structure alterations in the dDG through Western blotting, electron microscopy and immunofluorescence. Results: In the present study, we found that cocaine induced a decrease in the level of FAAH in the dDG and increased the level of AEA. A high level of AEA activated cannabinoid type 1 receptors (CB1Rs) and further triggered CB1R signalling activation and granule neuron dendritic remodelling, and these effects were reversed by blockade of CB1Rs in the brain. Furthermore, inhibition of FAAH in the dDG markedly increased AEA levels and promoted cocaine-associated memory formation through CB1R signalling activation. Conclusions: Together, our findings demonstrate that the lipase FAAH influences CB1R signalling activation and granule neuron dendritic structure alteration in the dDG by regulating AEA levels and that AEA and AEA metabolism play a key role in cocaine-associated memory formation. Manipulation of AEA production may serve as a potential therapeutic strategy for drug addiction and relapse prevention.